Impact on the Kidney of Pancreas Damage due to Streptozotocin-Induced Hyperglycemia - Prathita, Yana Aurora; Jusuf, Ahmad Aulia; Simadibrata, Christina; Djaali, Wahyuningsih; Viventius, Yoshua (Folia Medica Indonesiana, 2023)
Highlights: • This study observed the histology of pancreatic β-cell damage without any intervention to the kidneys of the animal models. • The histological analysis of the kidneys shows that STZ-induced animal models can be used for assessing kidney abnormalities due to hyperglycemia. • A scoring system for the histological analysis was developed to evaluate the changes in the kidney cells. Abstract The kidneys are one of the organs affected by microvascular complications due to diabetes mellitus. Hyperglycemia plays an important role in glomerular, mesangial cell, and tubular damage in the kidneys. Metabolic dysregulation, including hyperglycemia, initiates cellular damage in the kidneys. Streptozotocin (STZ) is a chemical compound that is known to damage pancreatic cells and cause hyperglycemia. This study aimed to examine the effects of hyperglycemia on the morphology of the kidneys. Kidney tissues were observed histologically using a light microscope. Samples were taken from the kidneys of experimental animals administered with STZ to induce hyperglycemia. Observation was performed afterwards to investigate any damage to pancreatic cells. A total of 12 kidney samples were divided into two groups: the control group and the STZ-induced group. The samples were prepared before staining with hematoxylin-eosin and Masson's trichrome. The endothelium, podocytes, mesangial cells, and basement membrane of the glomerulus were examined. The tubules of the kidneys were also examined, and the presence or absence of connective tissue formation in both groups was statistically tested. The results suggested a significant difference in tubular damage (p<0.05) and an insignificant difference in an increase in the damage of other components of the kidneys (p>0.05) in the STZ-induced group. Significant morphological changes were observed in the hyperglycemic renal tubules due to the administration of STZ. In conclusion, STZ-induced hyperglycemia caused damage to the kidney components but overall had no significant impact on the kidney.